(untitled) (Teacher’s World: Journal of Education and Research, 2023)
Addressing student problem behavior is a leading concern for educators as behavioral issues interfere with school engagement, academic achievement, and social relationships. This study aims to explore the factors of problem behavior. It includes 24 teachers and 20 students as study participants purposively selected from five conveniently selected non-government secondary schools in rural Kushtia. Focus Group Discussion and interviews were used to collect data. The data was analyzed following the inductive content analysis technique, and the findings were presented under key themes explored. The findings show that heterogeneous factors, including parental supervision, peer influence, school environment and teachers’ role and use of technology, have a significant influence on students’ problem behavior. Teacher’s World: Journal of Education and Research, Vol. 48(2), Dec 2022, p.142-156